How to assess agricultural innovation systems in a transformation perspective: a Delphi consensus study. Issue 2 (15th March 2022) - Toillier, Aurélie; Mathé, Syndhia; Saley Moussa, Abdoulaye; Faure, Guy
ABSTRACT: Purpose: This article explores to what extent a Delphi consensus study can help in designing a framework for assessing agricultural innovation systems (AIS), and this in a perspective of transformation of these systems in a diversity of countries. Approach: First, we reviewed the diversity of existing assessment methodologies in terms of their assessment rationales and associated epistemological and methodological debates. Second, we facilitated a process of framework design through an adapted group-based Delphi technique that we developed, based on an expert dialogue format with an initial online survey and six rounds of enriched controlled feedback. Findings: The adapted Delphi process appears to be effective since experts reached a consensus on a capacity-oriented assessment model with standardized and flexible components. Dissenting views remained but were suggested as a basis for further research, with a focus on the nature and use of high-level indicators and on ways facilitating the use of evidence by decision-makers in a capacity development perspective. Several factors that triggered and hindered consensus building during the Delphi process were detected. Practical implications: A number of lessons were drawn to enhance participation and consensus in further Delphi studies applied to framework design. Theoretical implications: Our study underscores the different worldviews on transformation and assessment of AIS. It opens the way for the use of group-based Delphi studies to initiate the co-production of knowledge on AIS science at the international level. Originality: The value of Delphi studies in addressing framework design issues has been little explored so far.